Focusing of sub-micrometer particles in microfluidic devices. Issue 1 (13th November 2019) - Zhang, Tianlong; Hong, Zhen-Yi; Tang, Shi-Yang; Li, Weihua; Inglis, David W.; Hosokawa, Yoichiroh; Yalikun, Yaxiaer; Li, Ming
Abstract : This work comprehensively reviews the fundamentals and applications of different types of microfluidic techniques for the focusing of sub-micrometer particles. Abstract : Sub-micrometer particles (0.10–1.0 μm) are of great significance to study, e.g., microvesicles and protein aggregates are targets for therapeutic intervention, and sub-micrometer fluorescent polystyrene (PS) particles are used as probes for diagnostic imaging. Focusing of sub-micrometer particles – precisely control over the position of sub-micrometer particles in a tightly focused stream – has a wide range of applications in the field of biology, chemistry and environment, by acting as a prerequisite step for downstream detection, manipulation and quantification. Microfluidic devices have been attracting great attention as desirable tools for sub-micrometer particle focusing, due to their small size, low reagent consumption, fast analysis and low cost. Recent advancements in fundamental knowledge and fabrication technologies have enabled microfluidic focusing of particles at sub-micrometer scale in a continuous, label-free and high-throughput manner. Microfluidic methods for the focusing of sub-micrometer particles can be classified into two main groups depending on whether an external field is applied: 1) passive methods, which utilize intrinsic fluidic properties without the need of external actuation, such as inertial, deterministic lateral displacement (DLD), viscoelastic and hydrophoretic focusing; and 2) active methods, where external fields are used, such as dielectrophoretic, thermophoretic, acoustophoretic and optical focusing. This article mainly reviews the studies on the focusing of sub-micrometer particles in microfluidic devices over the past 10 years. It aims to bridge the gap between the focusing of micrometer and nanometer scale (1.0–100 nm) particles and to improve the understanding of development progress, current advances and future prospects in microfluidic focusing techniques.